„Journey‟as an Exodus: The Refugee Vamoose in Khaled Hosseini‟sSea Prayer - Saju, Dona Maria; John, Rijo (International Journal of Psychosocial Rehabilitation, 2020)
The word ‘journey’ has several dimensions, especially in the current scenario infected with uncontainable epidemics such as civil wars, nuclear threats, religious terrorism and so on. Its end result is millions of innocent people murdered and others left with nothing but their remaining life, looking expectantly at the world and its benevolence to provide them an abode. For these hopeless beings, journey is not a pleasure trip, but an exodus – a forced exile from one’s land, leaving behind everything, without even the hope that they will make it to the end. Several writers across the globe have reacted to the refugee crisis, but what singularises Khaled Hosseini’s Sea Prayer is its short, yet heart- breaking illustration of the current refugee crisis. It is in the form of a letter written by a father to his son on the eve of a journey through sea. The sea crossing is going to be dangerous and the father worries about his son, the greatest treasure of his life. The work is inspired by the unfortunate incident of Alan Kurdi,the three year old Syrian refugee child who drowned in the Mediterranean Sea,while trying to reach the safe shores of Europe, in September 2015.There is always some uncertainty in journeys. One may begin his/her journey, but reaching the destination is unsure. This is more so in the case of refugees. Also, theyare uninvited people anywhere they go. The stories of their journey are accompanied by humiliation, rejection, insecurity and hopelessness. This article looks into the traumatic conditions of these people, who are often homogenously categorized as ‘refugees’, even though they come from different places and socio-economic and political backgrounds